Foraging Preference of Apis cerana F. and Apis mellifera L. to Broccoli under Caged and Open Conditions in Chitwan - Devkota, FR; Thapa, RB (Journal of the Institute of Agriculture and Animal Science, 2005)
A study was conducted to evaluate foraging behavior of Apis cerana F. and A. mellifera L. in broccoli blooms under caged and open conditions in Chitwan, Nepal during 1999-2000. The study showed that both the bee species preferred open plot for foraging and A. cerana F. foraged significantly (P < 0.05) higher number of broccoli flowers (an average of 11.39 and 12.11 flowers per minute) as compared to A. mellifera L. (an average of 9.03 and 10.89 flowers per minute) under caged and open conditions, respectively. The number of bees foraging per plant was not significantly different, showing broccoli bloom equally preferable to both honeybee species. Key words: Apis cerana F., A. mellifera L., foraging, broccoli blooms, open and caged plots J. Inst. Agric. Anim. Sci. 26:167-168 (2005)